Several Isoforms for Each Subunit Shared by RNA Polymerases are Differentially Expressed in the Cultivated Olive Tree (Olea europaea L.) - Fernández-Parras, Isabel; Ramírez-Tejero, Jorge Antolín; Luque, Francisco; Navarro, Francisco (Frontiers in Molecular Biosciences, 2021)
Plants contain five nuclear RNA polymerases, with RNA pol IV and V in addition to conserved eukaryotic RNA pols I, II and III. These transcriptional complexes share five common subunits, which have been extensively analyzed only in yeasts. By taking advantage of the recently published olive tree cultivar (Olea europaea L. cv. Picual) genome, we performed a genome-wide analysis of the genomic composition corresponding to subunits common to RNA pols. The cultivated olive tree genome is quite complex and contains many genes with several copies in the genome. We also investigated, for the first time, gene expression patterns for subunits common to RNA pols using RNA-Seq under different economically and biologically relevant conditions for the cultivar ‘Picual’: tissues/organs, biotic and abiotic stresses, and early development from seeds. Our results demonstrated the existence of a multigene family of subunits common to RNA pols, and a variable number of paralogs for each subunit in the olive cultivar ‘Picual’. Furthermore, these isoforms display specific and differentiated expression profiles depending on the isoform and growth conditions, which may be relevant for their role in olive tree biology.